Effect of dietary restriction and subsequent realimentation on hepatic oxidative phosphorylation in cattle - Porter, Richard (My University, 2021)
Compensatory growth (CG) is a naturally accelerated growth which occurs upon realimentation, following a prior period of dietary restriction. The process is harnessed worldwide as a management practice to reduce feed costs in beef cattle production. The objective of this study was to assess the potential contribution of hepatic cellular mitochondrial capacity to CG through global hepatic oxidative phosphorylation gene expression analyses as well as functional mitochondrial enzyme activity assays. Holstein–Friesian bulls were separated into two groups: (i) restricted feed allowance for 125 days (Period 1) (RES; n = 30) followed by ad-libitum feeding for 55 days (Period 2) or (ii) ad-libitum access to feed throughout (Periods 1 and 2) (ADLIB; n = 30). At the end of each period, 15 animals from each treatment group were slaughtered and hepatic tissue was collected. Tissue samples were subjected to RNAseq and spectrophotometric analysis for the functional assessment of mitochondria. RES and ADLIB groups grew at 0.6 kg/day and 1.9 kg/day, respectively, during Period 1. During Period 2, the RES group underwent CG growing at 2.5 kg/day, with ADLIB animals gaining 1.4 kg/day. Oxidative phosphorylation genes were differentially expressed in response to both dietary restriction and CG. Spectrophotometric assays indicated that mitochondrial abundance was greater in animals undergoing dietary restriction at the end of Period 1 and subsequently reduced during realimentation (P < 0.02). Results indicate that mitochondrial capacity may be enhanced during dietary restriction to more effectively utilize diet-derived nutrients. However, enhanced mitochondrial capacity does not appear to be directly contributing to CG in cattle.
PUBLISHED
Keywords: cattle; Compensatory growth (CG); reduce feed costs; cattle; Compensatory growth (CG); reduce feed costs; Genes & Society; Animal Nutrition; Education